Agri-food supply chain resilience: An exploration of influencing factors based on fuzzy-DEMATEL-ISM analysis - Min Zhang; Jining Yang (PLoS ONE, 2025)
Increasingly frequent disruptions from diseases, disasters, and human activities pose a significant challenge to the resilience of the agri-food supply chain (AFSCRE). This study systematically explores the factors influencing AFSCRE and their mechanisms of action by integrating fuzzy Decision-Making Trial and Evaluation Laboratory (DEMATEL) and Interpretative Structural Modeling (ISM). Based on bibliometrics and expert interviews, a three-dimensional indicator system (12 key factors) contains flexibility, agility, and visibility. Triangular fuzzy numbers were used to process expert rating data, and combined with the Converting Fuzzy Numbers into Crisp Scores (CFCS) defuzzification method to establish a total influence matrix. The strength of the influence relationships between factors was determined through the setting of appropriate thresholds, which ultimately results in a five-layer hierarchical structure. The research results show that: level of application of digital technologies, information system maturity, information sharing and synergies, data sharing and analysis capacity and risk management capacity constitute the deep driving factors; degree of simplification of the supply chain structure and level of inventory management are the direct surface factors, presenting isolated characteristics. The study proposes resilience enhancement strategies such as supplier diversification, blockchain traceability technology embedding, and multi-body collaborative decision-making mechanisms, which provide decision support for coping with climate change and public health emergencies.